Aspectos do nicho de regeneração em duas espécies de Gochnatia (Asteraceae) em comunidade de cerrado - Ribeiro, Jonathan Wesley Ferreira [UNESP] (2014)
Understanding which factors determine the ecologica l distribution of plants is very important for the conservation of their species. Th e Gochnatia barrosii and G. polymorpha species exhibit distinct patterns of distribution in the Cerrado phytophysiognomies, with the species G. polymorpha occupying a larger number of microHhabitats in relation to G. barrosii . Given these facts, it was aimed to evaluate if the preferential habitats for G. barrosii and G. polymorpha species are distinct for water, temperature or light during the initial grow th stages, and also if the regeneration niche is related to ecological distrib ution of species in different vegetation types from Cerrado. We evaluated the ger minative potential of the cypselae of both species submitted to different env ironmental factors (temperature, light quality, water availability) under controlled conditions. Moreover, we evaluated the response of growth, physiological attributes an d morphoanatomical leaf attributes from plants submitted to different shading levels u nder greenhouse conditions. The species G. polymorpha presented higher thermal amplitude, with high germi nation rates; it even showed better responses facing diffe rent situations, with lesser light sensibility and higher hydric stress tolerance than G. barrosii . Both species presented phenotypic plasticity, being able to change their g rowth, morphoanatomical and physiological leaf characteristics in response to d ifferent levels of shading. However, the G. polymorpha species showed greater phenotypic plasticity compa red to G. barrosii . Therefore, it was concluded that the water, light and temperature are limiting for germination cypselae, being light an important environmental filter also for the initial development, and thus, for the spatial dist ribution of these species in the Cerrado vegetations. The germination characteristic s and development of plants in...